Prevalence of diabetes in Malaysia and usefulness of HbA1c as a diagnostic criterion - Wan Nazaimoon, W.M.; Md Isa, S.H.; Wan Mohamad, W.B.; Khir, A.S.; Kamaruddin, N.A.; Kamarul, I.M.; Mustafa, N.; Ismail, I.S.; Ali, O.; Khalid, B.A.K. (2013)
AIM: The prevalence of diabetes mellitus among Malaysians aged â¥ 30 years of age has increased by more than twofold over a 20-year period. This study aimed to determine the current status and to evaluate the diagnostic usefulness of the HbA1c cut-off point of 48 mmol/mol (6.5). METHODS: Using a two-stage stratified sampling design, participants aged â¥ 18 years were recruited from five zones selected to represent Malaysia. An oral glucose tolerance test was performed on all those not known to have diabetes. RESULTS: A total of 4341 subjects were recruited. By World Health Organization criteria, the prevalence of diabetes mellitus was 22.9; of that percentage, 10.8 was known diabetes and 12.1 was newly diagnosed diabetes. Diabetes was most prevalent amongst Indians (37.9) and Malays (23.8). Prevalence of new diabetes mellitus was only 5.5 (95 CI 4.9-6.3) when based on the HbA1c diagnostic criteria of 48 mmol/mol (6.5) and, although the cut-off point was highly specific (98.1), it was less sensitive (36.7) compared with 45 mmol/mol (6.3), which showed the optimal sum of sensitivity (42.5) and specificity (97.4) in identifying new diabetes mellitus. CONCLUSION: This study recorded an overall diabetes prevalence of 22.6, almost a twofold increase from 11.6 reported in 2006. This was likely attributable to the higher prevalence of new diabetes (12.1) diagnosed following an oral glucose tolerance test. An HbA1c of 45 mmol/mol (6.3) was found to be a better predictive cut-off point for detecting new diabetes in our multi-ethnic population.